Torrumbarry irrigation district. Map 8,. Koondrook - Victoria. Department of Agriculture ([Melbourne] : Dept of Agriculture, 1973)
Includes table of soil type groups and explanatory notes to symbols.
Indexes to soil maps and soil types.
Keywords: Soils -- Victoria -- Koondrook -- Classification -- Maps; Soils -- Victoria -- Torrumbarry Irrigation District -- Classification -- Maps; Koondrook (Vic.) -- Maps; Torrumbarry Irrigation District (Vic.) -- Maps